Exercise awareness and barriers after spinal cord injury - Gorgey, Ashraf S (Baishideng Publishing Group Inc, 2014)
Exercise is an essential element in managing several of the non-communicable diseases after spinal cord injury (SCI). Awareness of the importance of prescribing a customized exercise program that meets the goals of persons with SCI should be highly considered in the rehabilitation community. The barriers of implementing specific exercise program as well as the factors that may mask the outcomes of regular exercise regimen need to be continuously addressed as a part of patients’ rehabilitation care. The focus of this editorial is to encourage the medical community to consider routine physical activity as one of the necessary vital signs that needs to be routinely checked in patients with SCI. Providing education tips, nutritional counseling and engaging in recreational programs may provide motivational route to the community of SCI. This may result in reinforcing active lifestyle in survivors with SCI as well as to reduce the impact of chronic life threatening medical disorders.